A Mixed Thermosensitive Hydrogel System for Sustained Delivery of Tacrolimus for Immunosuppressive Therapy - Hsiu-Chao Lin; Madonna Rica Anggelia; Chih-Chi Cheng; Kuan-Lin Ku; Hui-Yun Cheng; Chih-Jen Wen; Aline Yen Ling Wang; Cheng-Hung Lin; I-Ming Chu (MDPI AG, 2019)
Tacrolimus is an immunosuppressive agent for acute rejection after allotransplantation. However, the low aqueous solubility of tacrolimus poses difficulties in formulating an injection dosage. Polypeptide thermosensitive hydrogels can maintain a sustained release depot to deliver tacrolimus. The copolymers, which consist of poloxamer and poly(l-alanine) with l-lysine segments at both ends (P−Lys−Ala−PLX), are able to carry tacrolimus in an in situ gelled form with acceptable biocompatibility, biodegradability, and low gelling concentrations from 3 to 7 wt %. By adding Pluronic F-127 to formulate a mixed hydrogel system, the drug release rate can be adjusted to maintain suitable drug levels in animals with transplants. Under this formulation, the in vitro release of tacrolimus was stable for more than 100 days, while in vivo release of tacrolimus in mouse model showed that rejection from skin allotransplantation was prevented for at least three weeks with one single administration. Using these mixed hydrogel systems for sustaining delivery of tacrolimus demonstrates advancement in immunosuppressive therapy.